IMPLEMENTATION OF ISLAMIC EDUCATION AND DA'WAH WASATHIYAH GENERATION Z WITH QUR'ANIC INSIGHT IN FACING SOCIETY 5.0 - Nurita, Fika Wahyu; Perawironegoro, Djamaluddin (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Delivering Islamic education ineffectively increases the risk of fostering radical actions. Technology serves as a tool to expand the reach of da'wah across diverse groups. In the era of globalization, there is an opportunity for preachers to enhance creativity and innovation in conveying their messages. However, there is a need to improve da'wah activities, including resources and facilities. This study aims to assess the implementation of Wasathiyah education and da'wah among millennials, integrating an understanding of the Al-Quran within Society 5.0. The challenges faced are growing more intricate. The research utilized a descriptive analysis method with literature review techniques. The findings reveal that Islamic education for millennials is adapting to rapid technological advancements, showing resilience against extremist influences in the name of Islam. It becomes challenging to label someone with a differing opinion as incorrect. Preachers must exhibit creativity and innovation to adapt to technological progress, ensuring that Generation Z develops an interest in Islamic teachings.